HUBUNGAN KEKUATAN OTOT LENGAN DENGAN KEMAMPUAN PASSING ATAS PADA PERMAINAN BOLA VOLI SISWA SMA NEGERI 1 MENUI - Erna Elisa; Saifu Saifu; Muhammad Rusli (universitas halu oleo, 2020)
The purpose of this study was to determine the correlation of arm muscle strength with long service ability of badminton games at the students of sport science in academic year 2017, department of sports science, faculty of teacher training and education, halu oleo university. The population in this study were all students of sport science in academic year 2017, department of sports science, faculty of teacher training and education, halu oleo university, amounted to 73 people consist of 65 boys and 8 girls. Sample in this study was carried out by purposive sampling technique that is after being selected based on gender obtained 65 boys, then able to done of long service totaling 32 students who were sampled in this study. The instrument is used to measure of arm muscle strength by push-up test for 30-second, while to measure of long service ability with a long service by passing the shuttlecock on the net test. Based on the product moment correlation test on the observed variables, it can be shown that there is a significant correlation between arm muscle strength and long service ability of badminton games, where rₓᵧ> 0.4 rtable (0.05: 32 = 0.349), with coefficient of determination (r2) = 0.16 or 16%. Based on value interpretation of r, it can be explained that the correlation between arm muscle strength and long service ability is correlated, but the correlation is very weak or very low.Based on the results of this analysis, this study can be concluded that there is a correlation between arm muscle strength with long service ability of badminton games at the students of sport science in academic year 2017, department of sports science, faculty of teacher training and education, halu oleo university. The result extreme limit gives an understanding that long service ability of badminton games not only determined by arm muscle strength, but also is determined by other factors to 84% that including agility, speed, accuracy, coordination, balance, flexibility, reaction and endurance.